The oesophageal string test: a novel, minimally invasive method measures mucosal inflammation in eosinophilic oesophagitis. Issue 10 (15th August 2012) - Furuta, Glenn T; Kagalwalla, Amir F; Lee, James J; Alumkal, Preeth; Maybruck, Brian T; Fillon, Sophie; Masterson, Joanne C; Ochkur, Sergei; Protheroe, Cheryl; Moore, Wendy; Pan, Zhaoxing; Amsden, Katie; et al.
Abstract : Objective: Eosinophil predominant inflammation characterises histological features of eosinophilic oesophagitis (EoE). Endoscopy with biopsy is currently the only method to assess oesophageal mucosal inflammation in EoE. We hypothesised that measurements of luminal eosinophil-derived proteins would correlate with oesophageal mucosal inflammation in children with EoE. Design: The Enterotest diagnostic device was used to develop an oesophageal string test (EST) as a minimally invasive clinical device. EST samples and oesophageal mucosal biopsies were obtained from children undergoing upper endoscopy for clinically defined indications. Eosinophil-derived proteins including eosinophil secondary granule proteins (major basic protein-1, eosinophil-derived neurotoxin, eosinophil cationic protein, eosinophil peroxidase) and Charcot–Leyden crystal protein/galectin-10 were measured by ELISA in luminal effluents eluted from ESTs and extracts of mucosal biopsies. Results: ESTs were performed in 41 children with active EoE (n=14), EoE in remission (n=8), gastro-oesophageal reflux disease (n=4) and controls with normal oesophagus (n=15). EST measurement of eosinophil-derived protein biomarkers significantly distinguished between children with active EoE, treated EoE in remission, gastro-oesophageal reflux disease and normal oesophagus. Levels of luminal eosinophil-derived proteins in EST samples significantly correlated with peak and mean oesophageal eosinophils/high power field (HPF), eosinophil peroxidase indices and levels of the same eosinophil-derived proteins in extracts of oesophageal biopsies. Conclusions: The presence of eosinophil-derived proteins in luminal secretions is reflective of mucosal inflammation in children with EoE. The EST is a novel, minimally invasive device for measuring oesophageal eosinophilic inflammation in children with EoE.